2021
DOI: 10.1108/ijssp-08-2021-0196
|View full text |Cite
|
Sign up to set email alerts
|

Does flexible work arrangements decrease or increase turnover intention? A comparison between the social exchange theory and border theory

Abstract: PurposeMore companies embrace flexible work arrangements (FWA) as one of their employee retention strategies, yet its effectiveness is not consistent. Generally, past researchers use the social exchange theory to explain how FWA lowers turnover intention, while the rest adopts the border theory to justify why FWA can be ineffective. Here, the authors compare the competing theories for the first time to differentiate the theoretical reasoning of three forms of FWA (flex time, flex leave and homeworking). Two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
(133 reference statements)
1
12
0
Order By: Relevance
“…Organizational commitment is considered as the main driver of employee turnover intention (Tsen et al, 2021). According to Chang et al (2013), organizational commitment is the most significant factor that influences turnover intention.…”
Section: Organizational Commitment and Turnover Intentionmentioning
confidence: 99%
“…Organizational commitment is considered as the main driver of employee turnover intention (Tsen et al, 2021). According to Chang et al (2013), organizational commitment is the most significant factor that influences turnover intention.…”
Section: Organizational Commitment and Turnover Intentionmentioning
confidence: 99%
“…In summary, the integration of COR theory and SET predicts that an organisation’s investment in telecommuting is a crucial resource that not only protects employees from workplace stressors, such as fear of COVID-19 and turnover (Choi, 2019 ; Jamal et al, 2021 ) but also fosters a sense of obligation among employees to reciprocate with positive workplace behavior and attitudes (Tsen et al, 2022 ). Thus, following COR theory and SET, we predict that telecommuting is related to fear of COVID-19 and ER.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Choi ( 2019 ) found that employees exhibit positive attitudes and less voluntary turnover if given flexible work arrangements. Tsen et al ( 2022 ) found that employees who perceived themselves as job independent and had access to flexible work and Flexi leave had lower turnover intention. Van Dyne et al ( 2007 ) argue that organisations use telecommuting as a way to attract and retain qualified professionals.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative work arrangements (Johnson et al, 2008 ; Mas & Pallais, 2017 ), once considered a privilege, have become a necessity as employers and employees attempt to cope with the COVID-19 pandemic. Such arrangements include flexible work hours, flexible work location (Tsen et al, 2021a ), and even flexible career paths. Alternative work arrangements such as flexible work hours have been found to impact employees' health and retention rates as well (Shifirin & Michel., 2021 ; Tsen et al, 2021b ).…”
Section: Study 2: Job Pursuit Intentionsmentioning
confidence: 99%